2012
DOI: 10.1530/eje-11-0894
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of the DI genotype of the angiotensin-I converting enzyme and association of the II genotype with insulin resistance in polycystic ovary syndrome

Abstract: Objective: The polycystic ovary syndrome (PCOS) is a common and complex disease with unclear pattern of inheritance, characterized by an androgen excess, while hyperinsulinemia and insulin resistance (IR) are common features of the syndrome. The angiotensin I converting enzyme (ACE) insertion (I)/deletion (D) gene polymorphism was proved to be involved in many pathophysiological conditions, including hypertension and IR. Design: The purpose of this study was to evaluate the involvement of the ACE gene polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Compared to the control cohort, both the homozygous insertion genotype ( P = 0.021) and the homozygous deletion genotype ( P = 0.015) showed a moderate increase in gliomas ( Table 3 ). Such frequency alterations of the two homozygous genotypes of a glioma-associated gene were observed for the first time in the present study, although similar changes in homozygous genotypes also have been encountered in other non-cancer disorders [ 40 , 41 ]. Moreover, the decrease in heterozygous genotype frequency in gliomas compared to either controls ( P = 0.005), or non-glioma cancers ( P = 0.020), suggests a protective role being played by the heterozygous genotype in gliomas and this is a characteristic of loci that are under the influence of balancing selection [ 27 ].…”
Section: Discussionsupporting
confidence: 86%
“…Compared to the control cohort, both the homozygous insertion genotype ( P = 0.021) and the homozygous deletion genotype ( P = 0.015) showed a moderate increase in gliomas ( Table 3 ). Such frequency alterations of the two homozygous genotypes of a glioma-associated gene were observed for the first time in the present study, although similar changes in homozygous genotypes also have been encountered in other non-cancer disorders [ 40 , 41 ]. Moreover, the decrease in heterozygous genotype frequency in gliomas compared to either controls ( P = 0.005), or non-glioma cancers ( P = 0.020), suggests a protective role being played by the heterozygous genotype in gliomas and this is a characteristic of loci that are under the influence of balancing selection [ 27 ].…”
Section: Discussionsupporting
confidence: 86%
“…To the best of our knowledge, this is the first study to assess the possible role of ACE I/D polymorphisms in the aetiopathogenesis of PCOS. [16,18,26].…”
Section: Discussionmentioning
confidence: 99%
“…I), additive (DD vs. II), dominant (DD and DI vs. II) and recessive (DD vs. DI and II) genetic model. Since Koika et al 20 suggested that the DI genotype was associated with increased risk of PCOS in Greeks, a codominance (DI vs. DD and II) genetic model was also adopted. Furthermore, subgroup analyses stratified by ethnicity were also performed.…”
Section: Discussionmentioning
confidence: 99%